Применение валавира в комплексном лечении герпетических кератитов - Завгородняя, Н. Г.; Михальчик, Т. С.; Михальчик, С. В.; Коваленко, Н. Н.; Завгородня, Наталія Григорівна; Михальчик, Сергій Валерійович; Zavgorodnyaya, N. G.; Mihalchik, T. S.; Mihalchik, S. V.; Kovalenko, N. N.; Михальчик, Тетяна Сергіївна (My University, 2012)
Under supervision there were 25 patients at the age of 30–76 years with monocular defeat of the cornea, the caused virus of the simple herpes, receiving treatment in eye branch of Regional clinical hospital of Zaporozhye within 2010–11. The work purpose was studying of efficiency of application of a preparation valaciclovira - Valavir® in complex treatment of patients with herpes keratitis. Duration of treatment in the basic group made from 13 till 22 days (17,4±2,3). Terms of treatment at persons who did not receive Valavir®, fluctuated from 16 till 28 days (24,3±4,2). Thus, use in complex treatment of patients of a preparation of Valavir® allows to raise efficiency of rehabilitation of persons with the given pathology, promotes process acceleration resolution infiltration corneas and to reduction of terms of patients treatment.
Efficiency of complex treatment herpeseratitis with inclusion in scheme valaciclovira
Keywords: ophtalmoherpes; valaciclovir; quality of treatment; keratitis